Study on Retail Marketing of Various and Human Factors Affecting It: Exploring the Impact of Human Factors on Retail Marketing (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Retail Marketing defined as“individuals or groups, acquiring, using and disposing of products, services,ideas or experiences” (Arnould, Price & Zinkha, 2004). There are numbers ofdifferent theories explaining Retail Marketing (Statt, 1997; Blackwell,Minrard, and Engel, 2006; Chaudhuri, 2006) and a huge amount of literaturecurrently exists (Grunert 2002; Botonaki, Ploymeros, Tsakorodou, & Mattas,2006; Friese, Wanke, and Plessner, 2006). There are different number ofcharacteristics, which can impact on Retail Marketing (Figure 1), whichincludes from demographic variables to purchase and consumption behaviours.